2015
DOI: 10.1128/jvi.03719-14
|View full text |Cite
|
Sign up to set email alerts
|

Vpu Is the Main Determinant for Tetraspanin Downregulation in HIV-1-Infected Cells

Abstract: Tetraspanins constitute a family of cellular proteins that organize various membrane-based processes. Several members of this family, including CD81, are actively recruited by HIV-1 Gag to viral assembly and release sites. Despite their enrichment at viral exit sites, the overall levels of tetraspanins are decreased in HIV-1-infected cells. Here, we identify Vpu as the main viral determinant for tetraspanin downregulation. We also show that reduction of CD81 levels by Vpu is not a by-product of CD4 or BST-2/ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…Consistent with this idea, Vpu has been shown to inhibit HIV-1 cell-to-cell transmission in both BST2-expressing (69) and BST2-deficient (70) cells and is selected against during long-term in vitro culture, perhaps resulting in enhanced cell-to-cell transmission (71). A similar evolutionary compromise has been proposed for the Vpu-targeted tetraspanin molecules (27). Tetraspanins are surface membrane proteins that have been reported to benefit HIV-1 by preventing the cell-to-cell fusion events that lead to the formation of syncytia (72) yet hinder HIV-1 by decreasing infectivity when packaged into virions (73).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Consistent with this idea, Vpu has been shown to inhibit HIV-1 cell-to-cell transmission in both BST2-expressing (69) and BST2-deficient (70) cells and is selected against during long-term in vitro culture, perhaps resulting in enhanced cell-to-cell transmission (71). A similar evolutionary compromise has been proposed for the Vpu-targeted tetraspanin molecules (27). Tetraspanins are surface membrane proteins that have been reported to benefit HIV-1 by preventing the cell-to-cell fusion events that lead to the formation of syncytia (72) yet hinder HIV-1 by decreasing infectivity when packaged into virions (73).…”
Section: Discussionmentioning
confidence: 48%
“…They include immunoreceptors, such as human leukocyte antigen C (HLA-C) (20), NK-T-B antigen (NTB-A) (21), CD1d (22), and poliovirus receptor (PVR) (23); homing molecules, like CCR7 (24) and CD62L (25); sodium-coupled neutral amino acid transporter 1 (SNAT1) (26); and numerous members of the tetraspanin family (27). These downregulations lead to a wide array of immunomodulatory effects, including immune evasion and metabolic dysfunction.…”
mentioning
confidence: 99%
“…By virtue of this adaptor function, Nef affects many central processes in HIV target cells. This includes modulation of cellular transport pathways leading to downregulation of an array of receptors from the surface of infected cells (4)(5)(6), which, e.g., prevents superinfection (7,8) and lysis of productively infected cells by cytotoxic T or NK cells (9,10). HIV-1 Nef also alters the response of CD4 T lymphocytes to stimulation via the T cell receptor (TCR), and modulation of the resulting cellular signaling pathways is thought to increase virus replication in the infected host (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Particularly, surface expression of tetraspanin protein family members, such as CD37, CD53, CD63, CD81, and CD231, was reduced by both Vpu and Nef. 75 Lambele et al 76 also demonstrated that two tetraspanin molecules, CD81 and CD82, are downmodulated by HIV-1 Vpu (strain NL4-3), and specifically, that CD81 is reduced independently of the serine residues at positions 53 and 57 ( Figure 1(b)). Interestingly, these tetraspanin proteins including CD37, CD53, CD63, CD81, and CD231 have the ability to modulate HIV-1 infectivity by incorporating into nascent released viral particles 77 and impair cell-to-cell HIV-1 infection.…”
Section: Other Cellular Transmembrane Proteinsmentioning
confidence: 90%